Benchmarking clinical outcomes and the immunocatabolic phenotype of chronic critical illness after sepsis in surgical intensive care unit patients. Issue 2 (February 2018) - Stortz, Julie A.; Mira, Juan C.; Raymond, Steven L.; Loftus, Tyler J.; Ozrazgat-Baslanti, Tezcan; Wang, Zhongkai; Ghita, Gabriela L.; Leeuwenburgh, Christiaan; Segal, Mark S.; Bihorac, Azra; Brumback, Babette A.; Mohr, Alicia M.; et al.
Abstract : BACKGROUND: A growing number of patients survive sepsis but remain chronically critically ill. We sought to define clinical outcomes and incidence of chronic critical illness (CCI) after sepsis and to determine whether selected biomarkers of inflammation, immunosuppression, and catabolism differ between these patients and those that rapidly recover (RAP). METHODS: This 3-year prospective observational cohort study (NCT02276417) evaluated 145 surgical intensive care unit patients with sepsis for the development of CCI (≥14 days of intensive care unit resource utilization with persistent organ dysfunction). Patient clinical demographics, outcomes, and serial serum/urine samples were collected for plasma protein and urinary metabolite analyses. RESULTS: Of 145 sepsis patients enrolled, 19 (13%) died during their hospitalization and 71 (49%) developed CCI. The CCI patients were significantly older (mean, 63 ± 15 vs. 58 ± 13 years, p = 0.006) and more likely to be discharged to long-term acute care facilities (32% vs. 3%, p < 0.0001), whereas those with RAP were more often discharged to home or a rehabilitation facility. Six-month mortality was significantly higher in CCI as compared with RAP cohort (37% vs. 2%; p < 0.01). Multivariate logistic regression modeling revealed delayed onset sepsis (>48 hours after admission; odds ratio [OR], 10.93; 95% confidence interval [CI], 4.15–28.82]), interfacility transfer (OR, 3.58; 95% CI, 1.43–8.96), vasopressor-dependent septic shock (OR, 3.75; 95% CI, 1.47–9.54), and Sequential Organ Failure Assessment score of 5 or greater at 72 hours (OR, 5.03; 95% CI, 2.00–12.62) as independent risk factors for the development of CCI. The CCI patients also demonstrated greater elevations in inflammatory cytokines (IL-6, IL-8, IL-10), and biomarker profiles are consistent with persistent immunosuppression (absolute lymphocyte count and soluble programmed death ligand 1) and catabolism (plasma insulin-like growth factor binding protein 3 and urinary 3-methylhistidine excretion). CONCLUSION: The development of CCI has become the predominant clinical trajectory in critically ill surgical patients with sepsis. These patients exhibit biomarker profiles consistent with an immunocatabolic phenotype of persistent inflammation, immunosuppression, and catabolism. LEVEL OF EVIDENCE: Prognostic, level II. Abstract : Supplemental digital content is available in the text.